Effect of Reward and Punishment on Employee Performance with Leadership Style as an Intervening Variable: Study on PT Angkasa Pura II International Airport Branch Office Sultan Syarif Kasim II Pekanbaru - Rifqi, Ahmad; Siregar, Prima Andreas; Ghifary, Arya Hadi (PT. Riset Press International, 2025)
This study aimed to test and determine the effect of reward and punishment on employee performance with leadership style as an intervening variable at PT Angkasa Pura II International Airport Branch Office Sultan Syarif Kasim II Pekanbaru. The population of this study includes all employees of the finance and human resources division of PT Angkasa Pura II Pekanbaru. Sampling in this study used a saturated sampling technique (census), which converts all members of the population into samples so that the number of samples in this study was 37. The data analysis method used in this research is the structural equation modelling–partial least square (SEM-PLS) analysis method with WarpPLS software version 7.0. The results of this study indicate that rewards and punishment have a positive and significant influence on employee performance and leadership style. In addition, the mediating role of leadership style also has a significant impact on the effect of rewards and punishments on employee performance.